Informação e mentalidade empreendedora: estudos de caso com acadêmicos de universidades no Brasil e Canadá - Flavia de Souza Magalhães Fonseca (2023)
This work brings to the field of Information Science two case studies that have information and academic entrepreneurship as central themes, researched in the light of the Biology of Knowing. The research aims to identify the origin of information related to the formation of the entrepreneurial mindset of academics from the Federal University of Minas Gerais (UFMG), in Brazil, and Western University, in Canada, where the international Ph.D. exchange program was carried out. It also aims to characterize the external environments – academic and family – to which these subjects are exposed, considering the level of incentive to entrepreneurship practices; and to characterize used information sources, informational behavior and social interactions involved in decision-making processes. Based on case studies, the research has a qualitative and descriptive characteristic, and the data were collected from documentary research and the methodology of structured in-depth interviews, with entrepreneurs selected by non-probabilistic sampling. The interview script questions were constructed considering the life history of the participants, seven professors interviewed at UFMG and seven former students interviewed at Western University. The primary evidence is that the information that determines the entrepreneurial mindset was built, in the case of the two samples of respondents, from two interacting factors: the biological characteristics of the research subjects, openness to the entrepreneurial initiative, and the initial influence of the family environment, where the information is in remarkable life experiences or memories related to words and attitudes of motivation of parents and relatives. The academic environment also proved to be extremely important for the development of an entrepreneurial mindset, which can encourage or even present itself as a barrier to the creation of new businesses. In this respect, the academic environments analyzed were quite different: Western University has more experience with the practice of entrepreneurial education. In terms of information sources and information behavior, there was a great deal of similarity in the search processes and use of information by the two groups of interviewees, who prefer digital sources, interactions with peers or people close to them, and exchange of more informal information than formal, in a systematized dynamic that is part of the day-to-day work. As a main conclusion, the relevance of entrepreneurial education is highlighted, whose bases are fundamental for the formation of the knowing and decision-making subject, in constant interaction with other subjects and the environments where they transit and influenced since childhood by non-objectified information in sources or documents but transmitted through the family and resignified in adulthood in contact with the university.